Antibodies Targeting KSHV gH/gL Reveal Distinct Neutralization Mechanisms - Fricke, Thomas; Großkopf, Anna K.; Enßer, Armin; Backovic, Marija; Hahn, Alexander S. (Viruses, 2022)
Kaposi’s sarcoma herpesvirus (KSHV) is associated with a significant disease burden, in particular in Sub-Sahara Africa. A KSHV vaccine would be highly desirable, but the mechanisms underlying neutralizing antibody responses against KSHV remain largely unexplored. The complex made of glycoproteins H and L (gH/gL) activates gB for the fusion of viral and cellular membranes in all herpesviruses. KSHV gH/gL also interacts with cellular Eph family receptors. To identify optimal antigens for vaccination and to elucidate neutralization mechanisms, we primed mice with recombinantly expressed, soluble gH/gL (gHecto/gL) that was either wildtype (WT), lacking defined glycosylation sites or bearing modified glycosylation, followed by boosts with WT gHecto/gL. We also immunized with a gL-gHecto fusion protein or a gHecto-ferritin/gL nanoparticle. Immune sera neutralized KSHV and inhibited EphA2 receptor binding. None of the regimens was superior to immunization with WT gHecto/gL with regard to neutralizing activity and EphA2 blocking activity, the gL-gHecto fusion protein was equally effective, and the ferritin construct was inferior. gH/gL-targeting sera inhibited gB-mediated membrane fusion and inhibited infection also independently from receptor binding and gL, as demonstrated by neutralization of a novel KSHV mutant that does not or only marginally incorporate gL into the gH/gL complex and infects through an Eph-independent route.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Fusion; GH/gL; Herpesvirus entry; HHV-8; KSHV; Neutralizing antibodies